Pneumomediastinum following dental extraction - a case report in a tertiary hospital - Christian Haddad; Mohamad Awali; Salim Ismail; Getachew Gudero; Jacques Choucair (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Pneumomediastinum is a rare complication described following dental extraction, especially of the third molar. 212 case reports were described in the English literature since 1960. We describe a case report of a 19-year-old girl who presented to the emergency department with subcutaneous emphysema. Investigations showed the presence of pneumomediastinum. The patient was admitted for surveillance with no antibiotic therapy given due to the improvement seen the following day.